2017
DOI: 10.1016/j.brainres.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent ethanol exposure selectively alters the expression of Gα subunit isoforms and RGS subtypes in rat prefrontal cortex

Abstract: Chronic alcohol exposure induces pronounced changes in GPCR-mediated G-protein signaling. Recent microarray and RNA-seq analyses suggest associations between alcohol abuse and the expression of genes involved in G-protein signaling. The activity of G-proteins (e.g. Gαi/o and Gαq) is negatively modulated by regulator of G-protein signaling (RGS) proteins which are implicated in drugs of abuse including alcohol. The present study used 7 days of chronic intermittent ethanol exposure followed by 24 hour withdrawal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…GPCRs are negatively regulated by a class of GTPases termed regulator of G-protein signaling (RGS) [ 242 ]. RGS5, a potent negative regulator of Gα q and Gα i , structurally consists of a conserved RGS domain that binds to the corresponding Gα subunit and dephosphorylates the active GTP-bound Gα subunit via the GTPase-stimulating activity of the RGS domain [ 243 , 244 ].…”
Section: Gpcrs-mediated Autophagy In Ischemic Strokementioning
confidence: 99%
“…GPCRs are negatively regulated by a class of GTPases termed regulator of G-protein signaling (RGS) [ 242 ]. RGS5, a potent negative regulator of Gα q and Gα i , structurally consists of a conserved RGS domain that binds to the corresponding Gα subunit and dephosphorylates the active GTP-bound Gα subunit via the GTPase-stimulating activity of the RGS domain [ 243 , 244 ].…”
Section: Gpcrs-mediated Autophagy In Ischemic Strokementioning
confidence: 99%
“…The groups were administered study agents for 18 days. 12 At the end of the experiment, all animals were anesthetized with ketamine hydrochloride (50 mg/kg; Ketalar ® , Pfizer, Turkey) and xylazine hydrochloride (15mg/ kg; Rompun ® , Bayer, Turkey) administered intraperitoneally. The animals were fixed by transcardial perfusion under anesthesia with heparinized saline solution followed by 10% neutral-buffered formalin.…”
Section: Application Of Experimentsmentioning
confidence: 99%
“…Recently, Lin group reported that the prediction model of ovarian cancer constructed using RGS family genes was likely to be important to the clinical decision making and the personalized treatment of patients with ovarian cancer [12]. Beyond that, many researches focus mostly on the expression and pathogenesis of speci c members of RGS gene family including RGS2, RGS4, RGS5, RGS12, RGS17 et al [13][14][15]. However, the study on RGS gene family in KIRC is none.…”
Section: Introductionmentioning
confidence: 99%